Developing an Eclipse Crossword-Based E-Module to Improve Students’ Critical Thinking in Plant Reproduction - Akbar Handoko; Diamah Adilah; Mazalena Mazalena; Raicha Oktafiani; Nukhbatul Bidayati Haka; Aryani Dwi Kesumawardani; Laila Puspita; Ismi Rakhmawati (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2026)
The integration of digital learning media in biology instruction is increasingly important for enhancing students’ higher-order thinking skills, particularly in topics that involve abstract concepts and complex terminology, such as plant reproductive systems. This study aimed to develop and evaluate the feasibility, practicality, and effectiveness of a crossword puzzle-based e-module using Eclipse Crossword to improve the critical thinking skills of Grade IX students at Madrasah Tsanawiyah Negeri 01 Bandar Lampung. Employing a Research and Development design adapted from Borg and Gall, the study involved expert validation, readability testing, student response analysis, and an effectiveness test using a pretest–posttest control group design. Data were collected through validation sheets, questionnaires, observation, documentation, and critical thinking tests, and were analyzed using percentage scores, N-Gain, paired sample t-test, and independent sample t-test. The results showed that the developed e-module was highly feasible, with validation scores of 89.3% from media experts and 91.7% from material experts. The readability test indicated that 90% of students perceived the module as clear, engaging, and easy to use. The effectiveness test demonstrated a significant improvement in students’ critical thinking skills, with the experimental class achieving a higher posttest mean score than the control class and a moderate N-Gain score of 0.4403, compared with 0.1371 in the control class. Students also responded positively to the module, indicating that it was interactive, challenging, and helpful for understanding biological concepts. These findings imply that Eclipse Crossword-based e-modules can serve as an innovative and practical digital learning medium to support critical thinking development in biology learning.